Elaboración de biocarbón obtenido a partir de la cáscara del cacao y raquis del banano - Marin Armijos, Federy Javier (Machala : Universidad Técnica de Machala, 2019)
The disposal of organic residues obtained from crops such as the rachis of bananas and the husk of the cob of cocoa are not efficiently managed, and this research proposes the possibility of using these wastes as fertilizers through the manufacture of bio char by pyrolysis. Reason for the objective of the research was to design an oven to produce bio char, based on the process of pyrolysis, using the rachis of banana and cocoa husk previously dried as raw material of easy access and abundant in the province of El Oro (Ecuador), place where the work was carried out. The results indicate that the process is feasible showing a better homogenization of the product in terms of its incineration to the bio char obtained from the cocoa husk.
La disposición de los residuos orgánicos obtenidos de las cosechas como el raquis del banano y la cáscara de la mazorca del cacao, no son gestionados de forma eficiente, planteando esta investigación la posibilidad de utilizar estos desechos como abonos mediante la fabricación de biocarbón por pirolisis. Motivo por el objetivo de la investigación fue diseñar un horno para producir biocarbon, basados en el proceso de pirolisis, utilizando al raquis del banano y cáscara del cacao previamente secos como materia prima de fácil acceso y abundante en la provincia de El Oro (Ecuador), lugar donde se llevó a cabo el trabajo. Los resultados indican que el proceso es factible mostrando una mejor homogenización del producto en cuanto a su incineración al biocarbón obtenido de la cáscara del cacao.
Keywords: RESIDUOS; COSECHA; PIROLISIS; CALCINACIÓN